From Data to Empowerment: How the Integration of a Digital Health Surveillance System Supports Women’s Engagement in Healthcare Sector in the Kurdistan Region of Iraq - Cicala, Mariagrazia; Cutini, Rita; Qadir , A. Sivar; Salih , O. Shahla; Alhanabadi , H. H. Luma; Tofiq, A. Berivan; Emberti , Gialloreti Leonardo; Adhama , S. L. Rafal; Moramarco, Stefania (Journal of Cultural Analysis and Social Change, 2026)
In Iraq, persistent inequalities between the sexes continue to limit women's access to education, employment, and decision-making roles, particularly within the health sector. In the northern region of Iraq, the Kurdistan Region (KRG) - a context characterized by institutional fragility, unreliable health data and strong demographic pressure - the digitization of health information systems represents a strategic opportunity to improve governance and promote women's empowerment. The present study examines the experience of the KRG-DHIS2, an epidemiological e-health system for data collection developed by the University of Rome Tor Vergata (Italy) in collaboration with the Ministry of Health of the Kurdistan Regional Government. It highlights the initiative’s dual impact: strengthening epidemiological surveillance and enhancing women’s roles as both producers and users of health data. Since 2016, the project has involved 98 health facilities, trained more than 900 operators–51% of whom are women–and supported female participation in advanced training programs, including doctoral studies and technical leadership activities. The results reinforce the evidence that integrating a digital system, coupled with investment in local capacities, can improve data quality, promote more equitable decision-making, and strengthen women’s presence in health governance processes. The experience of the KRG illustrates that women’s participation in managing health information systems can help position digital health as a catalyst for equity and sustainable development.